Gat1 (Gaba:Na(+):Cl(−)) Cotransport Function: Steady State Studies in Giant Xenopus Oocyte Membrane Patches - Lu, Chin-Chih (The Rockefeller University Press, 1999)
Neurotransmitter transporters are reported to mediate transmembrane ion movements that are poorly coupled to neurotransmitter transport and to exhibit complex “channel-like” behaviors that challenge the classical “alternating access” transport model. To test alternative models, and to develop an improved model for the Na(+)- and Cl(−)-dependent γ-aminobutyric acid (GABA) transporter, GAT1, we expressed GAT1 in Xenopus oocytes and analyzed its function in detail in giant membrane patches. We detected no Na(+)- or Cl(−)- dependent currents in the absence of GABA, nor did we detect activating effects of substrates added to the trans side. Outward GAT1 current (“reverse” transport mode) requires the presence of all three substrates on the cytoplasmic side. Inward GAT1 current (“forward” transport mode) can be partially activated by GABA and Na(+) on the extracellular (pipette) side in the nominal absence of Cl(−). With all three substrates on both membrane sides, reversal potentials defined with specific GAT1 inhibitors are consistent with the proposed stoichiometry of 1GABA:2Na(+):1Cl(−). As predicted for the “alternating access” model, addition of a substrate to the trans side (120 mM extracellular Na(+)) decreases the half-maximal concentration for activation of current by a substrate on the cis side (cytoplasmic GABA). In the presence of extracellular Na(+), the half-maximal cytoplasmic GABA concentration is increased by decreasing cytoplasmic Cl(−). In the absence of extracellular Na(+), half-maximal cytoplasmic substrate concentrations (8 mM Cl(−), 2 mM GABA, 60 mM Na(+)) do not change when cosubstrate concentrations are reduced, with the exception that reducing cytoplasmic Cl(−) increases the half-maximal cytoplasmic Na(+) concentration. The forward GAT1 current (i.e., inward current with all extracellular substrates present) is inhibited monotonically by cytoplasmic Cl(−) (K (i), 8 mM); cytoplasmic Na(+) and cytoplasmic GABA are without effect in the absence of cytoplasmic Cl(−). In the absence of extracellular Na(+), current–voltage relations for reverse transport current (i.e., outward current with all cytoplasmic substrates present) can be approximated by shallow exponential functions whose slopes are consistent with rate-limiting steps moving 0.15–0.3 equivalent charges. The slopes of current–voltage relations change only little when current is reduced four- to eightfold by lowering each cosubstrate concentration; they increase twofold upon addition of 100 mM Na(+) to the extracellular (pipette) side.